1980
DOI: 10.1111/j.1600-0447.1980.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Community reactions to mental disorders – A KEY INFORMANT STUDY IN THREE DEVELOPING COUNTRIES

Abstract: Attitudes towards mental disorders have been studied in rural areas of Sudan and Northern India and an urban area of the Philippines using standardized interviews with key informants. On average each informant knew by name 3.6 individuals who corresponded to descriptions provided of common mental disorders. The conditions most frequently identified were mental retardation (in all three areas), alcohol and drug related problems (in the Sudanese and Philippines areas) and acute psychosis (in the Indian area). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 3 publications
3
40
0
1
Order By: Relevance
“…A prevalence of 18.2 per 1000 was found using the cluster sampling method while the key-informant method estimated epilepsy to be 3.6 per 1000. Other studies using key informants to find patients were done by Thorburn et al 31 and Wig et al 32 with similar conclusions to Kaamugisha et al 25 The NMS source in our study found a prevalence of 7.9 per 1000 using a similar approach. This is double the prevalence found by Kaamugisha et al 25 based on key informants, while the DTD found a prevalence ratio (16.0 per 1000) quite close to their result by cluster sampling method which found 18.2 per 1000.…”
Section: Discussionsupporting
confidence: 75%
“…A prevalence of 18.2 per 1000 was found using the cluster sampling method while the key-informant method estimated epilepsy to be 3.6 per 1000. Other studies using key informants to find patients were done by Thorburn et al 31 and Wig et al 32 with similar conclusions to Kaamugisha et al 25 The NMS source in our study found a prevalence of 7.9 per 1000 using a similar approach. This is double the prevalence found by Kaamugisha et al 25 based on key informants, while the DTD found a prevalence ratio (16.0 per 1000) quite close to their result by cluster sampling method which found 18.2 per 1000.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, so few psychotic patients were detected in the screening exercise that it is not possible to draw conclusions about the health workers' ability to diagnose such patients. The disinclination of psychotic patients to seek help at primary health facilities is clearly related to the attitudes and perceptions of mental illness which we have studied in a community survey, reported elsewhere (Wig et al 1980). Reaching psychotic patients who do not present spontaneously at primary health care facilities calls for active case finding by primary health workers in the community.…”
Section: Diagnostic Ratings By Health Staff and Their Accuracymentioning
confidence: 78%
“…The results are being published separately (Giel et al in preparation). A survey of community attitudes and perceptions has also been carried out (Wig et al 1980 …”
Section: The Study Areasmentioning
confidence: 99%
“…This entails interviewing individuals whose social positions make them influential and bring them into contact with a large number of people. For example, Wig et al, (1980) carried out a key informant study in three developing countries to study the perceptions of mental illness and their consequences in the community. The results were used to select priorities and design interventions to promote community involvement.…”
Section: Introductionmentioning
confidence: 99%